2021
DOI: 10.1007/s11356-021-12431-w
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxicity induced by fine particulate matter (PM2.5) via mitochondria-mediated apoptosis pathway in rat alveolar macrophages

Abstract: Although positive associations exist between ambient particulate matter (PM 2.5 ; diameter ≤ 2.5 μm) and the morbidity and mortality rates for respiratory diseases, the biological mechanisms of the reported health effects are unclear. Considering that alveolar macrophages (AM) are the main cells responsible for phagocytic clearance of xenobiotic particles that reach the airspaces of the lungs, the purpose of this study was to investigate whether PM 2.5 induced AM apoptosis, and investigate its possible mechani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 68 publications
1
11
0
Order By: Relevance
“…Previous studies have demonstrated that PM 2.5 decreased macrophages viability and increased apoptosis through ROS overproduction 38,39 . PM 2.5 could aggravate lung injury by inducing apoptosis of alveolar macrophages, 40 and aggravate lipid accumulation, mitochondrial damage and apoptosis in foam cells of RAW264.7 cells 41 . Thus, PM 2.5 ‐induced ROS production and apoptosis were measured to evaluated the effect of coelonin pretreatment, the results showed that coelonin pretreatment effectively reduced ROS production, reduced apoptosis and necrosis levels in RAW264.7 cells and J774A.1 cells.…”
Section: Discussionmentioning
confidence: 98%
“…Previous studies have demonstrated that PM 2.5 decreased macrophages viability and increased apoptosis through ROS overproduction 38,39 . PM 2.5 could aggravate lung injury by inducing apoptosis of alveolar macrophages, 40 and aggravate lipid accumulation, mitochondrial damage and apoptosis in foam cells of RAW264.7 cells 41 . Thus, PM 2.5 ‐induced ROS production and apoptosis were measured to evaluated the effect of coelonin pretreatment, the results showed that coelonin pretreatment effectively reduced ROS production, reduced apoptosis and necrosis levels in RAW264.7 cells and J774A.1 cells.…”
Section: Discussionmentioning
confidence: 98%
“…Exposure to NIST1648a resulted in much more potent activation of genes associated with the two forms of programmed cell death, apoptosis and necroptosis, than exposure to LAp120. The literature indicates that both of these forms occur as a result of exposure to PM [ 58 , 59 ]. Apoptosis can be triggered by external signals as a result of activation of death receptors by appropriate ligands (e.g., FasL/FasR and TNF/TNFR1) or intracellular processes associated with DNA damage or oxidative stress (reviewed in [ 60 ]).…”
Section: Discussionmentioning
confidence: 99%
“…The results of gene profiling obtained in this study indicated that exposure to both forms of PM induced mainly the extrinsic apoptotic pathway as evidenced by the most pronounced expression of genes of this pathway (i.e., Tnf , Fas and Daxx ) and the relatively lower enrichment of the term named the p53 signaling pathway [ 60 , 61 ]. It should be noted, however, that a large part of the reports in the literature indicate the prevalence of the intrinsic apoptotic pathway associated with increased ROS synthesis due to the fact of PM exposure (e.g., [ 58 ]).…”
Section: Discussionmentioning
confidence: 99%
“…These factors recruit and stimulate other immune cells, alveolar epithelial cells, endothelial cells, and fiber cells to secrete many cytokines and adhesion factors, forming an inflammatory cascade reaction [ 15 ]. In addition, it can also cause oxidative stress through various pathways [ 16 ] and induce apoptosis [ 17 ], pyroptosis [ 18 ], or autophagy [ 19 ]. The alveolar surfactant is also destroyed [ 20 ], resulting in alveolar collapse and shrinkage, and then lung tissue damage is aggravated.…”
Section: Introductionmentioning
confidence: 99%